Receptors of Advanced Glycation End Product (RAGE) Suppression Associated With a Preserved Osteogenic Differentiation in Patients With Prediabetes - Phimphilai, Mattabhorn; Pothacharoen, Peraphan; Chattipakorn, Nipon; Kongtawelert, Prachya (Frontiers in Endocrinology, 2022)
Type 2 diabetes is widely documented for osteogenic differentiation defect and impaired bone quality, which is related to the skeletal accumulation of advanced glycation end products (AGEs). Prediabetes is a condition in which hyperglycemia is lower than the threshold for the diagnosis of diabetes. Prediabetic animal models consistently demonstrate impaired osteogenic differentiation and deteriorated bone microarchitecture. However, no evidence shows defects in osteoblast development and skeletal effects of AGEs in prediabetic individuals. Therefore, it remains to be elucidated whether impaired osteogenic differentiation ability and altered cellular response to AGEs occur in patients with prediabetes. This cross-sectional study included 28 patients with prediabetes as defined by impaired fasting glucose criteria, fasting plasma glucose (FPG) between 100-125 mg/dL, and 17 age-matched normoglycemic controls to elucidate osteogenic differentiation and AGER expression in the PBMC derived from those individuals. The PBMC-isolated from both groups showed similar rates of expression of osteoblast-specific genes including ALPL, BGLAP, COL1A1, and RUNX2/PPAR (89.3 % and 88.2 %, p = 1.000), and showed comparable levels of expression of those genes. By using age- and pentosidine-matched normoglycemic individuals as references, the PBMC-isolated from prediabetic patients demonstrated lower expression of both AGER and BAX/BCL2. The expression of AGER and BAX/BCL2 significantly correlated to each other (r = 0.986, p < 0.0001). The multivariate analysis demonstrated that serum pentosidine is an independent risk factor for AGER expression. With logistic regression analysis, the area under the ROC curve (AUC) for serum pentosidine at the cut-off level of 2.1 ng/mL and FPG at 100 mg/dL, which is a cut-off point for prediabetes, was significantly higher for predicting AGER expression than that of serum pentosidine alone (0.803 vs 0.688, p = 0.048), indicating that serum pentosidine was a good predictor of AGER expression in prediabetic individuals. In conclusion, this study demonstrated a preserved osteogenic differentiation in the PBMC derived from prediabetic individuals. In addition, those PBMC with preserved osteogenic differentiation potential showed the suppression of both cellular RAGE and apoptotic-related signals. Serum pentosidine was an independent risk factor for cellular RAGE expression and is conceivably a good predictor for AGER suppression in prediabetic individuals.